A Meta-analysis of Combined Aspiration Catheter and Stent Retriever versus Stent Retriever Alone for Large-Vessel Occlusion Ischemic Stroke - Schartz, D.A.; Ellens, N.R.; Kohli, G.S.; Akkipeddi, S.M.K.; Colby, G.P.; Bhalla, T.; Mattingly, T.K.; Bender, M.T. (American Journal of Neuroradiology, 2022)
BACKGROUND: The efficacy of combined aspiration catheter and stent retriever compared with stent retriever alone for the treatment of large-vessel occlusion acute ischemic stroke is unclear.PURPOSE: Our aim was to conduct a systematic literature review and meta-analysis on several metrics of efficacy comparing aspiration catheter and stent retriever with stent retriever alone.DATA SOURCES: MEDLINE and the Cochrane Library Databases were searched. Randomized controlled trials and case-control and cohort studies were included.STUDY SELECTION: Ten comparative studies were included detailing a combined 1495 patients with aspiration catheter and stent retriever and 1864 with stent retrievers alone.DATA ANALYSIS: Data on first pass effect (TICI 2b/2c/3 after first pass), final successful reperfusion (modified TICI ≥2b), and 90-day functional independence (mRS ≤ 2) were collected. Meta-analysis was performed using a random-effects model.DATA SYNTHESIS: There was a pooled composite first pass effect of 40.8% (611/1495) versus 32.6% (608/1864) for aspiration catheter and stent retriever and stent retriever alone, respectively (P < .0001). Similarly, on a meta-analysis, aspiration catheter and stent retriever were associated with a higher first pass effect compared with stent retriever alone (OR = 1.63; 95% CI, 1.20–2.21; P = .002; I2 = 72%). There was no significant difference in composite rates of successful reperfusion between aspiration catheter and stent retriever (72.8%, 867/1190) and stent retriever alone (70.8%, 931/1314) (P = .27) or on meta-analysis (OR = 1.31; CI, 0.81–2.12; P = .27; I2 = 82%). No difference was found between aspiration catheter and stent retriever and stent retriever alone on 90-day functional independence (OR = 1.02; 95% CI, 0.77–1.36; P = .88; I2 = 40%).LIMITATIONS: This study is limited by high interstudy heterogeneity.CONCLUSIONS: On meta-analysis, aspiration catheter and stent retriever are associated with a superior first pass effect compared with stent retriever alone, but they are not associated with statistically different final reperfusion or functional independence.AISacute ischemic strokeASRcombined aspiration catheter and stent retrieverBGCballoon-guide cathetereTICIexpanded TICImTICImodified TICIFPEfirst pass effectLVOlarge-vessel occlusionSRstent retriever